The Influence of Human Resources' Knowledge, Skills and Abilities on Business Sustainability: (Study on Wooden Batik Craftsmen, Krebet) - Nany Noor Kurniyati; Bangun Putra Prasetya (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Tourism deposits have great potential in prospering the surrounding community and improving the economy. The ability and awareness of the community in managing the tourism potential that exists around is certainly very petrified for the economic life of local residents. The purpose of this research is to find out how Human Resources affect business sustainability. This study uses a quantitative approach with the population of this study is all Batik Micro, Small and Medium Enterprises (MSMEs) in the Krebet Tourism Village Area, Bantul Regency. Simplified sampling techniques. This technique is carried out by selecting samples freely according to the ease and access to data. The results of the study showed that the increase in knowledge did not have a significant effect on the business sustainability variable. Meanwhile, other variables such as HR Skills and Abilities have a significant impact on the business sustainability variable. the Adjusted R Square value is 0.764 or 76.4%. This shows that the improvement of knowledge, skills and abilities of human resources towards business sustainability is 76.4% while the remaining 23.6% is explained by other variables outside the model.